PENGARUH LIKUIDITAS, KEBIJAKAN DIVIDEN, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MAKANAN DAN MINUMAN DI BEI - Sitorus, Winda; Purnasari, Nina; Br Sitompul, Melda Sari; Saragih, Jhosua Billy Gredo; Sitompul, Haryani Pratiwi (JURNAL LENTERA BISNIS, 2026)
This study aims to examine the effect of liquidity, dividend policy, leverage, and company size on earnings management in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. This study uses secondary data in the form of financial reports taken from the official IDX website. In this study, 140 samples were processed using SPSS. The data analysis techniques used were the classical assumption test, namely the normality test, heteroscedasticity test, autocorrelation test, and multicollinearity test. The results of this study indicate that the dependent variable does not affect the independent variables in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period.